A Thomistic account of natural understanding of the human good and practical truth - Van Dyke, JW (2022)
In this study I examine how the human being naturally comes to understand the human good and practical truth according to a Thomistic perspective. I begin with a claim that St. Thomas Aquinas draws from the Christian tradition as my starting premise: that the human being is created by God with an intellectual nature and natural intellectual aptitude to participate in God’s understanding and loving.